Home office: organizado e explicado - FREITAS, Kallew Guerreiro Rodrigues de; SANTOS, Lucas Ferreira dos; SANTANA, Nicole (104, 2023)
Este artigo busca levantar demais informações sobre uma variação do trabalho remoto, o home office, explicando de forma neutra, organizando esse regime trabalhista, para que mais organizações possam compreendê-lo, pois há um acervo muito pequeno de informações sobre. O trabalho contará com diversos meios metodológicos, como pesquisas bibliográficas e exploratórias, assim será possível gerar uma fonte segura e de qualidade sobre o assunto, servindo como uma consulta confiável as organizações que buscam entender melhor o home office.

This article seeks to survey furthermore information about a variety of the remote work, the home office, talking neutral form, organizing this work regime, so that more organizations could understand it, because there is a very small archive with data about it. The work will narrate with diverse methodological means, as bibliographical researches and exploratory, like this will possibly generate safe sources and quality about this topic, serving as a reliable consult to the organizations that seek to understand better the home office concept.
Home office: organized and explained
Keywords: Trabalho; Teletrabalho; Organização do trabalho; Gestão e Negócios